Analysis of Students’ Difficulties in Solving Mathematics Word Problems Based on VARK-Fleming Learning Styles - Anitasari; Ika Ratnaningrum; Tri Murtini (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze students’ difficulties in solving multiplication and division word problems based on the VARK-Fleming learning styles: visual, auditory, read/write, and kinesthetic. This mixed method research involved third-grade students of SDN Tambakaji 01 Semarang in the 2025/2026 academic year. Eight students (2 from each learning style) were selected for interviews using purposive sampling. Data were collected through the VARK questionnaire, essay type word problem tests, observation, interviews, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data reduction, display, and conclusion drawing. The results show that learning styles were dominated by auditory (33.33%), followed by read/write (29.17%), kinesthetic (20.83%), and visual (16.67%). Difficulties varied by learning style. Visual students mainly struggled with understanding word problems (55.5%), conceptual understanding (41.6%), problem-solving skills (38.8%), and calculation (27.7%). Auditory students had difficulties in understanding word problems (40.2%) and calculation (31.9%). Read/write students struggled most with understanding word problems (47.6%) and calculation (38.0%). Kinesthetic students experienced major difficulties in understanding word problems (48.8%) and problem-solving skills (46.6%), while calculation and conceptual difficulties were relatively lower (14.2%). These difficulties were influenced by internal and external factors.